The Review Process and the Fates of Manuscripts Submitted to AMJ - Beyer, Janice M.; Chanove, Roland G.; Fox, William B. (Academy of Management Journal, 1995)
Four perspectives on the review processes of scientific journals were employed heuristically to Examine the AMJ review process from 1984 through 1987. Results indicated modest support for hypotheses derived from accumulative advantage and particularism perspectives and more substantial support for hypotheses derived from gatekeeping and reviewer style perspectives. Testing a new perspective that combined predictors of gatekeeping and of coaching styles yielded the strongest results. In effect, the AMJ review process selectively amplified what reviewers and editors considered desirable in submitted manuscripts.